Combining Ability And Heterosis In Snakegourd (Tricosanthes Cucurminata L) - Podder, R; Rasul, MG; Islam, AKMA; Mian, Mak; Ahmed, JU (Bangladesh Journal of Plant Breeding and Genetics, 2011)
A half diallel set of five parents and their 10 F1’s were studied to determine the combining ability and magnitude of heterosis for eight important characters in snakegourd at the experimental field of Bangabandhu Sheikh Mujibur Rahman Agricultural University during April to July, 2004. Combining ability analysis revealed that both general and specific combining ability variances were significant for all the characters except fruit diameter and fruit yield per plant. Predominance of additive gene action was noted for all the characters except days to first female flower where non-additive gene action was predominant. Parent P1 was the best general combiner for fruit yield and some yield contributing characters. Among the crosses P2 X P3, P1 X P2 and P1 X P4 were the best specific combiner for fruit yield and some of yield contributing characters. Both positive and negative heterosis was obtained of which few hybrids showed desirable and significant values. P2 X P5 showed the highest significant mid parental heterotic value for earliness and high yield whereas, P1 X P2, P2 X P3, P2 X P5 and P3 X P4 showed the highest significant better parent heterotic effect for earliness and high yield. Key words: Snakegourd (Trichosanthes cucurminata L.); combining ability; heterosis; fruit yield DOI: http://dx.doi.org/10.3329/bjpbg.v23i2.9318 Bangladesh J. Pl. Breed. Genet., 23(2): 1-6, 2010